1990
DOI: 10.1111/j.1365-2141.1990.00001.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐alpha‐induced morphological changes of megakaryocytes: a histomorphometrical study on bone marrow biopsies in chronic myeloproliferative disorders with excessive thrombocytosis

Abstract: Summary Interferon(rIFN)‐alpha, a successful therapeutic agent in the control of thrombocytosis, has been shown to suppress human megakaryopoiesis. We investigated bone marrow biopsies from 12 patients with thrombocytosis due to chronic myeloproliferative disorders. Prior to treatment as well as during rIFN‐alpha‐2c therapy, several morphometric parameters of megakaryopoiesis were evaluated. Megakaryocyte density decreased significantly in all patients, megakaryocyte size decreased in polycythaemia vera, agnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Common side effects of PEG-IFNα-2a+RBV therapy include anaemia, leucopoenia and thrombocytopenia (17)(18)(19). Ribavirin has haemolytic effects and often causes anaemia, whereas IFNα has been shown to suppress haematopoietic progenitor cells in the bone marrow to induce leucopoenia and thrombocytopenia (20)(21)(22). Likewise, our study showed a statistically significant decrease in Hgb levels and RBC, Pt, WBC and Ne counts (p<0,001).…”
Section: Discussionsupporting
confidence: 70%
“…Common side effects of PEG-IFNα-2a+RBV therapy include anaemia, leucopoenia and thrombocytopenia (17)(18)(19). Ribavirin has haemolytic effects and often causes anaemia, whereas IFNα has been shown to suppress haematopoietic progenitor cells in the bone marrow to induce leucopoenia and thrombocytopenia (20)(21)(22). Likewise, our study showed a statistically significant decrease in Hgb levels and RBC, Pt, WBC and Ne counts (p<0,001).…”
Section: Discussionsupporting
confidence: 70%
“…These observations suggests that IFN-a can change the PV disease course to the preproliferative phase [37]. IFN-a has also been shown to decrease the levels of cytokines such as platelet-derived growth factor, transforming growth factor-b, and others that play a role in the development and clinical symptomology of MPNs [38].…”
Section: Interferonmentioning
confidence: 92%
“…Although, as noted, PV is a clonal stem cell disorder; there have been case reports of the resumption of polyclonal hematopoiesis after rIFN-a therapy (C. Steimle et al, manuscript submitted for publication). 24,25 rIFN-a inhibits erythroid progenitors and erythroid burst-forming units in vitro, 26 and produces morphologic and biochemical changes in megakaryocytes, 27 including a decrease in megakaryocyte density, size, and proliferation. IFN inhibits megakaryocyte progenitor proliferation and reduces thrombopoietin-induced Mpl receptor signaling.…”
Section: Myelosuppressive Therapymentioning
confidence: 99%